THE EFFECTS OF LEARNING MODEL AND LEARNING MOTIVATION TOWARDS ENGLISH ACHIEVEMENT - Esti Ayu Ambarwati; Rifari Baron (Universitas Indraprasta PGRI, 2018)
This research is an experimental study of private vocational school in West Jakarta, academic year of 2018-2019. The number of sample is 60 students who taken randomly from several private vocational schools in East Jakarta. The purpose of this research are (1) to find out the effects of learning motivation towards improvement of the students English achievement. (2) To find out the effect of learning motivation towards improvement of the student English achievement. (3) Next, to find out simultaneous effects learning model and learning motivation towards improvement of the student English achievement. Collecting data are carried out by giving questioner , observation and a test. Data analysis used by a two-way anova method. The statistical test used t test and f test. The results of this research are (1) there is a significant effect of using learning model towards English achievement students of private vocational school in West Jakarta. It is proven by getting sig score = 0.004 < 0.05 and f test = 8.9673). (2) There is a significant effect of learning motivation towards English achievement students of private vocational school in West Jakarta. It is proven by getting sig score = 0.008 < 0.05 and f.test = 7.563. ( 3) There are significant effects of learning model and learning motivation towards English achievement students of private vocational school in West Jakarta. Those are proven by getting sig score = 0.015 < 0.05 and f test = 6.278Key words : Learning model, learning motivation, English achievement